Use Of Photovoltaic Solar Technology Study - Barbosa Urbano, Janett; Trujillo González, Faiver Humberto; Velásquez Perilla, Pablo Elías; Castellanos Contreras, José Ulises (Ingeniería Solidaria, 2011)
Solar technology is based on the physical principle of converting solar energy absorbed by a highly conductive material in electrical current. The materials used are semiconductors with a variety of structures; it is essential to achieve maximum energy capture with a minimal cost. This work presents the initial aspects of the project: “Feasibility to design a system for capturing, storing, distributing and usage of photovoltaic energy in Bogotá”, developed by the “Universidad Cooperativa de Colombia”’s Engineering Faculty. It explains the current norms related to implementation, testing and performance of photovoltaic solar panels, plus some related research performed by several institutions worldwide. It also presents control software’s preliminary elements for the photovoltaic system.
Keywords: solar collectors; solar energy; regulations; semiconductors; solar cells; photovoltaic; current; electricity